Secagem do resíduo industrial da acerola em leito de jorro: estudos fluidodinâmicos e análise do desempenho do secador - Souza Júnior, Francisco Escolástico de (2012)
In this research, the drying process of acerola waste was investigated by using a spouted bed drier. The process was conducted using high density polyethylene inert particles with the objective of producing an ascorbic acid-rich final product. The fruit waste was ground and used to prepare different water-maltodextrin suspensions. Initially, fluidynamical experiments were conducted in order to evaluate the feeding effect on the spouted bed drier fluidynamics behavior. The experimental planning 23 + 3 was used to investigate the effect of the following variables: solids concentration, drying air temperature, intermittence time, production efficiency, solids retention and product losses by elutriation of fine particles on drier walls. The effect of selected independent variables on the drier stability was also evaluated based on a parameter defined as the ratio between the feed suspension volume and the total inert particles volume. Finally, the powder quality was verified in experiments with fixed feed flow and varying air drying temperature, drying air velocity and intermittence time. It was observed that the suspension interferes in the spouted bed drier fluidynamics behavior, and higher air flow is necessary to stabilize the drier. The suspension also promotes the expansion of the spouted bed diameter, decreases the solid circulation and favors the air distribution at the flush area. All variables interfere in the spouted bed performance, and the solids concentration has a major effect on the material retention and losses. The intermittence time also has great effect on the stability and material retention. When it comes to production efficiency, the main effect observed was the drying air temperature. First order models were well adjusted to retention and losses data. The acerola powder presented ascorbic acid levels around 600 to 700 mg/100g. Similar moisture and ascorbic acid levels were obtained for powders obtained by spouted bed and spray drier. However, the powder production efficiency of the spray drier was lower when compared to spouted bed drier. When it comes to energetic analysis, the spray drier process was superior. The results obtained for spouted bed drier are promising and highly dependent on the operational parameters chosen, but in general, it is inferred that this drying process is adequate for paste and suspension drying